Elastisitas Transmisi Harga Daging Kerbau Rawa di Desa Sapala Kecamatan Paminggir Kabupaten Hulu Sungai Utara - Miranda Romaully Br. Sitanggang; Firdaus Firdaus (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2015)
This study evaluating the marketing aspect swamp buffalo meat is held in the Sapala village Paminggir District of Hulu Sungai Utara Regency. This village was chosen because there were many swamp buffalo traders and breeders. The research goal is to identify the elasticity of price transmission swamp buffalo in the study area. The elasticity of price transmission on buffalo meat marketing in the village Sapala Paminggir Hulu subdistrict North River is 3,089. Elasticity of price transmission represents less than one (Et < 1), meaning that a 1% change in the price at the consumerlevel will lead to a change in price by 0.281% at the producer level. This shows the price is relatively inelastic transmission. So the price changes at the consumer level will provide a little change in farmer prices it’s mean that marketing of buffalo swamp meat is not efficient.